Eyes and neck kinematic model analysis with limited human gestures (2020)
Human emotions such as happiness, sadness, despair, amazement among others are produced by the limbic system which causes the movement of the facial muscles as a result of those emotions. In the realization of Rudolf, the animatronic, was considered, the simulation, interpretation and imitation of human movements of eyes, neck and mouth, in order to respond immediately to the emotions of the human being. Each of these movements were analysed kinematically and dynamically by the Denavit-Hartenberg matrices. In order to imitate the facial gestures of a human, the dynamics of the eyes, their degrees of freedom (DOF), as well as the neck and lower jaw, were physically analysed in order to perfect the imitation of a human being. On the other hand, the neural system of real-time image storage, activation of actuators and facial recognition was made through programming in Python and decoding with the Raspberry Pi Hardware.